A Generalized Steady-State Growth Theorem - Andreas Irmen (Center for Economic Studies and ifo Institute (CESifo), 2013)
Uzawa's steady-state growth theorem (Uzawa (1961)) is generalized to a neoclassical economy that uses current output, e. g., to create technical progress or to manufacture intermediates. The difference between aggregate final-good production and these resources is referred to as net output. The new generalized steady-state growth theorem holds since net output exhibits constant returns to scale in capital and labor. This insight provides an understanding for why technical change is labor-augmenting in steady state even if capital-augmenting technical change is feasible. By example, this point is made for three recent growth models that allow for endogenous capital- and labor-augmenting technical change, namely, Irmen (2013), Acemoglu (2003), and Acemoglu (2009), Chapter 15. The reduced form of these models is shown to be consistent with the generalized steady-state growth theorem.
Keywords: E10; O10; O40; 330; steady-state growth; capital accumulation; Uzawa's Theorem; endogenous direction of technical change